2013
DOI: 10.1063/1.4804395
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive thermal transitions of nanoscale polymer samples using the bimetallic effect: Application to ultra-thin polythiophene

Abstract: A sensitive nanocalorimetric technology based on microcantilever sensors is presented. The technology, which combines very short response times with very small sample consumption, uses the bimetallic effect to detect thermal transitions. Specifically, abrupt variations in the Young's modulus and the thermal expansion coefficient produced by temperature changes have been employed to detect thermodynamic transitions. The technology has been used to determine the glass transition of poly(3-thiophene methyl acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Resonating micro- and nano-electromechanical systems (MEMS, NEMS) of different geometries have been utilized for a variety of applications such as oscillators and filters, as well as chemical, mass, and humidity sensors. However, research into probing thermal characteristics of samples deposited onto the sensors is still in its infancy with only a few proof-of-concept studies reported in the literature. All but one of these studies focus on polymers. Furthermore, the main limitations are the applied sample deposition methods: specialized spray or spin coating, ink jet printing, or melt infiltration are used to deposit the sample on the sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Resonating micro- and nano-electromechanical systems (MEMS, NEMS) of different geometries have been utilized for a variety of applications such as oscillators and filters, as well as chemical, mass, and humidity sensors. However, research into probing thermal characteristics of samples deposited onto the sensors is still in its infancy with only a few proof-of-concept studies reported in the literature. All but one of these studies focus on polymers. Furthermore, the main limitations are the applied sample deposition methods: specialized spray or spin coating, ink jet printing, or melt infiltration are used to deposit the sample on the sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, surface roughness is one of the ions movement determinant during oxidation and reduction cycles, i.e., explains how topography affects the charge exchange in these systems. [13][14][15]17 The results presented in this work represent a significant improvement with respect our initial approach that has allowed us overcoming previous limitations, whereas we kept reducing the gap between the experimental scales in which surfaces are studied and the feasible use of force field based techniques within reasonable computation times.…”
Section: Introductionmentioning
confidence: 93%
“…For this system, the remarkable influence of the film-air interface on the thermal properties was examined by comparing the response of nanosheets and bulk P3TMA powder. 163 Although P3TMA, which is soluble in tetrahydrofuran, chloroform and dimethylformamide, among a few others, does not form freestanding films, 164 the understanding of its properties is of great interest because, as it will be discussed in the next sub-section, P3TMA has been combined with conventional biodegradable polymers to fabricate different types of electroactive FsNMs with biomedical applications. Interestingly, the glass transition temperature determined using microcantilevers coated with ultra-thin P3TMA films resulted in 5.2 1C higher than that obtained for bulk powder samples.…”
Section: All-electroactive Conducting Polymers and Inorganic-electroa...mentioning
confidence: 99%